Women at the helm: Chief executive officer gender and patient experience in the hospital industry. Issue 3 (7th July 2021) - Silvera, Geoffrey A.; Clark, Jonathan R.
Abstract : Background: Health care scholars have recognized the important role leaders play in the improvement of health care delivery systems, yet few have explored the kind of leaders who make a difference or the conditions under which certain health care executives thrive. Recent work in the hospital industry suggests that the role of chief executive officer (CEO) gender may be particularly salient in the context of patient experience (Galstian, Hearld, O'Connor, & Borkowski, 2018). Purpose: In this article, we bring an explicit theoretical and empirical lens to the issue of CEO gender in the context of patient experience. Our framework provides an explanation of both why (differences between men and women in their tendency for relational orientation) and under what circumstances (the degree of complexity in the executive job environment) CEO gender is most influential. Methodology/Approach: We test these relationships using data on patient experience in 391 nonrural U.S. hospitals between 2007 and 2011. Our study relies on both archival (e.g., Hospital Consumer Assessment of Healthcare Providers and Systems survey) and collected (e.g., CEO characteristics) data. Fixed-effects regression models are used to estimate the relationship between CEO gender and the interpersonal care experience. Results: We find evidence that female CEOs improve the interpersonal care experience faster than male CEOs, particularly in the most complex executive job environments, that is, in the most populous urban environments, and in the largest hospital facilities. Conclusion: Our results not only support the notion that executives tend to rely on personal values and preferences but also that women have an apparent propensity for transforming health care organizations in the direction of patient centeredness, particularly in the most demanding circumstances. Practice Implications: Hospital boards seeking to improve the patient experience should give careful attention to promoting women to the role of CEO and consider how their own policies may be constraining both the promotion of female executives and the creation of more patient-centered health care organizations.